Edukasi Pemanfaatan Jahe Sebagai Terapi Tradisional Untuk Mengurangi Mual Muntah Pada Ibu Hamil Trimester Pertama Di Klinik Pratama Madina - Nadya Fitriani; Aswin Syahputra; Miki Afrida Wati (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Nausea and vomiting are common complaints experienced by pregnant women in the first trimester. If left unmanaged, these symptoms may develop into hyperemesis gravidarum, which poses risks to both mother and fetus. One non-pharmacological alternative is the use of ginger (Zingiber officinale) as a complementary therapy. This community service activity aimed to improve the knowledge and attitudes of pregnant women regarding the benefits of ginger decoction in reducing nausea and vomiting. The method included health education, hands-on practice in preparing ginger decoction, and pre-test and post-test evaluations. The activity was conducted at Pratama Madina Clinic, involving 45 first-trimester pregnant women. Results indicated a significant increase in knowledge, with pre-test scores averaging 4.53 and post-test scores rising to 8.33. The activity also led to positive behavioral changes and increased awareness of the safe use of herbal therapies during pregnancy. Ginger education proved to be an effective initiative for fostering social transformation within the pregnant women's community.